Autocrats in the United Nations General Assembly: A test of the decoy voting hypothesis - Martin Mosler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
I empirically examine whether autocratic governments use decoy voting in the United Nations General Assembly to hide repressive behavior of their regimes. Previous research has identified the State of Israel as a unique decoy. My sample includes votes on all 4,878 contested resolutions involving Israel between 1950 and 2018. The vote agreement rate of fully autocratic regimes with Israel is on average 3.2 percentage points or 18 percent of a standard deviation lower than among fully democratic governments for Israel- and Palestinian issues-related resolutions. The effect is more pronounced for resolutions that primarily deal with the State of Israel, with an estimated decline in voting alignment of 3.6 percentage points or 20 percent of a standard deviation. The results are consistent with the hypothesis that autocratic governments use resolutions against the only Jewish-majority state to fill the voting agenda and deflect attention from their regimes.
Keywords: F53; D72; D74; 330; United Nations; autocracy; ethics of governance; decoy; politicalalignment; Israel